Objective-C for iPhone developers [ a beginner's guide - Brannan, James A. (McGraw-Hill, 2010)
"Shows you how to use the Objective-C programming language, Apple's Foundation framework, the iPhone SDK, and the Xcode development environment. ... Real-world examples throughout the book correspond with downloadable Ccode projects and video tutorials so you can get started with your first app right away."